A comprehensive guide to pulmonary function tests for 1st-year medical students – Simplifying PFTS and their interpretation - Bashir, Mudasir; Garg, Neeru; Muzaffar, Maha; Nyiem, Mahpara; Jaan, Iram; Nida Nowreen (Asian Journal of Medical Sciences, 2024)
Pulmonary function tests (PFTs) constitute a set of non-invasive diagnostic procedures designed to evaluate the functional capabilities of the respiratory system. These tests hold pivotal significance in the identification, tracking, and treatment of diverse respiratory conditions, including asthma, chronic obstructive pulmonary disease, interstitial lung diseases, and restrictive lung disorders. This review article aims to provide medical students with a comprehensive overview of PFTs and their interpretation, offering valuable insights into their crucial role in the diagnosis and management of respiratory ailments.